2021
DOI: 10.22437/edumatica.v11i01.12373
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Students’ Communication Skills and Independence Through Realistic Mathematics Learning Assisted by Google Classroom

Abstract: The purpose and problem formulation of this research is to find out whether realistic mathematics learning assisted by google classroom can improve students' communication skills and independence. This research method is descriptive quantitative research. This research was conducted at SMP Negeri 1 Pangkat in February-March 2021 in the even semester of the 2020/2021 learning year. The sample in this study were 25 students who were taken from the total population of data and could represent the entire populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…For the implementation of Google Classroom in mathematics education, the results revealed that the use of Google Classroom has positively impacted learning. According to various studies, Google Classroom has enabled new experiences for students, increased their awareness of metacognition, improved their learning independence, and enhanced their understanding of mathematical concepts Susilo et al, 2019;Suryawan et al, 2021;Sundary et al, 2020;& Ari, 2020;Huda et al, 2019;Pasaribu, 2021). While most studies on the implementation of Google Classroom in mathematics education have reported positive effects on learning outcomes, a few studies did not find significant impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the implementation of Google Classroom in mathematics education, the results revealed that the use of Google Classroom has positively impacted learning. According to various studies, Google Classroom has enabled new experiences for students, increased their awareness of metacognition, improved their learning independence, and enhanced their understanding of mathematical concepts Susilo et al, 2019;Suryawan et al, 2021;Sundary et al, 2020;& Ari, 2020;Huda et al, 2019;Pasaribu, 2021). While most studies on the implementation of Google Classroom in mathematics education have reported positive effects on learning outcomes, a few studies did not find significant impacts.…”
Section: Discussionmentioning
confidence: 99%
“…10. (Pasaribu, 2021) Students' communication skills and independence improve due to realistic mathematics learning (PMR) aided by Google Classroom.…”
Section: Table 2 Implementation Of Google Classroom In Mathematics Ed...mentioning
confidence: 99%
“…Matematika merupakan pendidikan awal yang sangat berarti bagi setiap orang, oleh sebab itu seiring berkembangnya teknologi ilmu pengetahuan ini perlu lebih dipahami dan dimengerti (Supartik & Pasaribu, 2021). Di era globalisasi dan canggihnya teknologi yang berkembang saat ini sebagian dari siswa yang kurang meminati dalam pembelajaran matematika.…”
Section: Pendahuluanunclassified
“…Tentunya bagaimana cara agar dapat meningkatkan motivasi beprestasi siswa tidak lepas dengan bantuan guru sebagai pendidik di sekolah. Menurut hasil penelitian bahwa pembelajaran dengan pendekatan realistik matematika berbantuan google classroom dapat meningkatkan kemampuan komunikasi matematika siswa dan kemandirian belajar dengan persentase pengaruhnya sebesar 34% (Supartik & Pasaribu, 2021).…”
Section: Hasil Dan Pembahasanunclassified